THE ROLE OF SOCIAL MEDIA INFLUENCERS IN SHAPING CONSUMER BUYING BEHAVIOR IN THE ELECTRONICS MARKET (Журнал «Маркетинг», 2025)
This study examines how social media influencers affect consumer buying behavior in the electronics market. It focuses on three main influencer attributes — credibility, attractiveness, and expertise — that shape trust and purchase intention. The findings highlight that social media acts as a key driver of decision-making in the digital economy.